STUDIES IN POVERTY FISHERMEN IN PULAU RAJO INDERAPURA VILLAGE AIRPURA DISTRICT OF PESISIR SELATAN REGION - YULIADI, NOFRIDON; Juita, S.Pd. M.Si, Erna; Zuriyani, M.Si, Elvi (Pendidikan Geografi, 2014)
ABSTRACTÂ Â This study aims to obtain, information and an overview data of poverty in fishermen in Pulau Rajo Inderapura Village Airpura District of Pesisir Selatan Region about the social and economic life fishermen in Pulau Rajo Inderapura Village views of: 1) income, 2) the type of fishing gear, 3) cultural and capital.Type of this research is descriptive. Population in this study whole families (KK) fishermen in Pulau Rajo Inderapura Village totaling 405. Samples were taken by purposive random sampling technique with the proportion of 20 % that the sample amounted to 80 fishermen.The results of the study: 1) the income of fishermen in Pulau Rajo Inderapura Village as follows : revenue/month average of Rp 500.000 - Rp 1.000.000/month, fulfilling the needs of income as a fisherman is not enough, a second job with an income of Rp 500.000 - Rp 1.000.000/month and expenditures for basic needs generally Rp 500.000 - Rp 1.000.000/month, 2) type of fishing gear in the form of ones own rowboat, fishing tool most used is purse seine and own property. How has the fishing vessels generally with the help of the family, while the results obtained within 1 day of fishing on average 0-10 kg, 3) culture that exists in the lives of the fishermen community in farmers including traditional, time to go to sea generally the morning with a long working 6 hours / day, went to sea accompanied by a child. The response to the success of the other fishermen generally emulate the fishermen catch and catch the action if it gets that much is the same as weekdays and 4) capital owned by fishermen today is capital itself, the amount of capital of Rp1.000.000, the current capital of Rp 1.000.000 - Rp 2.000.000, the development effort is good enough, while capital is still perceived to be inadequate. The current capital including substandard and there is no get funding from the government